2015
DOI: 10.1038/srep12379
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Colonic Aberrant Crypt Foci by Novel Schiff Based Dichlorido(4-Methoxy-2-{[2-(Piperazin-4-Ium-1-Yl)Ethyl]Iminomethyl}Phenolate)Cd Complex in Azoxymethane-Induced Colorectal Cancer in Rats

Abstract: Schiff-based complexes as a source of cancer chemotherapeutic compounds have been subjected to the variety of anticancer studies. The in-vitro analysis confirmed the CdCl2(C14H21N3O2) complex possess cytotoxicity and apoptosis induction properties in colon cancer cells, so lead to investigate the inhibitory efficiency of the compound on colonic aberrant crypt foci (ACF). Five groups of adult male rats were used in this study: Vehicle, cancer control, positive control groups and the groups treated with 25 and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
4
10
0
Order By: Relevance
“…The gastric tissue was then sectioned at a thickness of 5 µm and stained with hematoxylin and eosin. 26 , 33 Light microscopy was used to assess the tissue sections for any histopathological deviations, such as hemorrhage, edema, necrosis, and congestion. Mucosal glycoproteins were also assessed by staining the gastric tissue with periodic acid–Schiff (PAS) stains.…”
Section: Methodsmentioning
confidence: 99%
“…The gastric tissue was then sectioned at a thickness of 5 µm and stained with hematoxylin and eosin. 26 , 33 Light microscopy was used to assess the tissue sections for any histopathological deviations, such as hemorrhage, edema, necrosis, and congestion. Mucosal glycoproteins were also assessed by staining the gastric tissue with periodic acid–Schiff (PAS) stains.…”
Section: Methodsmentioning
confidence: 99%
“…PCNA or Proliferating Cell Nuclear Antigen serves as a processivity-promoting factor in DNA replication and an uncharacteristic upsurge of PCNA leading to epithelial cell proliferation is an early manifestation of pre-neoplasia 68. Studies reveal that the cellular level of PCNA is actively controlled by p53 69.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal epithelial cell proliferation due to over expression of PCNA is an earlier indication of pre‐neoplasia . It is found that p53 can control DNA replication by modulating PCNA levels .…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that over expression of PCNA and suppression of apoptosis is involved in the progression of carcinoma formation by influencing a cascade of pathways . In addition to these, mutations of tumor suppressor protein p53, VEGF (by angiogenic pathway), mTOR signaling pathway, pro‐apoptotic protein Bax, and increased expression of anti‐apoptotic protein Bcl2 is found to be involved in the progression of colon cancer …”
Section: Introductionmentioning
confidence: 99%